Elektrownie wiatrowe a inwestycje celu publicznego - Koszowski, Michał (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
On 22 December 2011, the Ministry of Economy presented a draft law on Renewable Energy Resources (RES), which fits into the discussion on the recognition of wind power plant as an investment of a public purpose (IPP). The author is of an opinion on that a wind power plant cannot be considered as an IPP for legal, rather than technical reasons. The investor’s objective is to obtain an outline planning decision, not a decision on the location of an IPP, which might otherwise prolong the investment process.